La metáfora de la corporalidad en la guerra como dispositivo resiliente (2020)
This research/ intervention aims at observing the Colombian armed conflict from perspective of the psychological component of the ex-combatant’s interpretation. In this sense, it propounds to understand the narrative construction of resilience in relation to corporality and identity of an ex-combatant of the Farc-ep guerrilla, within the framework of the armed conflict in Colombia and taking into account the participant’s militancy. Methodologically, conversational and sensory scenarios were carried out, scenarios meant to organize the narrative as a vital tool, so as to inform and dynamize the process and the transition in the research and intervention context. The latter is the methodological core of research, since intervention fosters the resilience process through the emerging story; subsequently, the research/ intervention methodological resource was enriched with feedback form the theoretical modelling in order to create scenarios and strategies to facilitate the development of the encounter. The most representative results of the research were the construction of metaphors and reflections on the vital experience, the sense of balance as a figure of mental health, the story of the war wound as framed by corporality in the resilient process, and the family bond with the armed group.